The challenges of implementing the bachelor's Degrees offered by the Open University of Brazil at the Federal Institute of Mato Grosso in Cuiabá (Research, Society and Development, 2020)
This research, an initial part of a Postdoctoral internship at UCDB-MS, aims to trace the profile of professor formador of the Open University of Brazil/IFMT and verify the challenges for the implementation of undergraduate courses offered via UAB/IFMT - Campus Cuiabá - Octayde Jorge da Silva. To meet our objectives, we adopt a qualitative approach, of a descriptive-explanatory nature. To carry out the research, we first developed a mapping, with bibliographic and documentary research, about the offer of bachelor's degrees at UAB at the Cuiabá Campus of IFMT; in a second moment the application of an online questionnaire, in order to weave the profile of the research subjects participating in the process of implementation of the bachelor's courses of the UAB-IFMT in addition to verifying the challenges about these bachelor's degrees and finally, we articulate the collected data. We selected two offers as a research locus, the degree in Pedagogy and pedagogical complementation, both offered by the Cuiabá Campus, and applied the online questionnaire in the Teaching Trainers of these courses. The results obtained show that, although the Teacher Trainers are Masters and Doctors, the absence of a specific training to work with the platform and interact with the students of the courses surveyed was configured as one of the challenges for the implementation of these courses, contributing to the difficulty of interaction with the students and execution of some actions of the platform.